Valley of hope : the Sungai Buloh National Leprosy Control Centre - Phang, Siew Sia; Wong, Chau Yin (MCA Subang Division, 2006)
Leprosy - the mere mention of the word itself was enough to send a shiver down the spine during those days. Some even associated it with evil spirits and considered it a curse for those who contracted it as a punishment for doing something morally wrong. More often than not, the victims were subjected to abuse (both verbal and physical), prejudice and isolation. It is not difficult to imagine the feelings of the victims and the trauma they have to go through in coming to terms with their face. Leprosy is one of the oldest scourges of humankind. Accounts of disease similar to leprosy were found in ancient Egyptian papyrus inscription dated back to 1550 BC. In ancient India, leprosy was referred to as Kushtha. Instructions for its prevention were stated in the Vedas, written as early as 1400 BC. The disease appeared 54 times in the Bible. It was perhaps the most badly understood disease for a long time and its patients have suffered much of it. The cause of leprosy was not scientifically identified until 1873 when Dr Gerhad Hansen discovered the bacterium called Mycobacterium leprea. Thus, it is also known as the Hansen Disease. The bacteria is transmitted through droplets discharged from an untreated patient and it is not easily communicable. It may only be contracted through prolonged close contact with an infected person who had not been properly treated or who does not undergo a regular medical treatment. Leprosy is the least infectious of all infectious diseases. It was only until the post-war years that effective medication was introduced. As it affects the victims' peripheral nerves and skin, the disease can cause deformities and disfigurements to patients of an advanced stage. To them, besides having to endure the physical torment, the feeling of loss, fear and prejudice and rejection by the society at large were more traumatic than anything else.